Analytical study of sustainability in ready-made clothes - Al-Qurashi, Manahil Mansour Omar; Al-Thabiti, Naglaa Jaber Dhifallah (Journal of Humanities & Social Sciences, 2024)
Human beings have been by nature since ancient times exploiters of development to achieve their wealth and resources and the outputs in their various forms to overcome the deficit and poverty and aspire to wealth by their development practices, but neglecting the environmental aspect. The research dealt with the study of the reality of sustainability in the ready-made clothes industry by analysing sustainable practices in luthe production stages of ready-made clothes for several factories in the Kingdom of Saudi Arabia, specifically in Makkah Al-Mukarramah region (Jeddah - Taif). To understand the concept of sustainability and the practices followed by factories in the field of ready-made clothing and in terms of studying the current situation to reach the methods followed in the different production stages and the extent to which they achieve sustainability, the research also aims to identify the factors affecting the production of clothing products and contributing to increasing waste and environmental pollution, and trying to contribute by putting appropriate proposals to achieve sustainability in factories through exploiting the remnants of fabrics and raw materials. The research consisted of five chapters. The most crucial results of the research were that most of the methods used in the stages of production and the extent to which they achieved sustainability in the “environmental dimension” were the stage of examining the cloth by 25.5%, followed by the second stage is the “aggregation stage” with a rate of 21.6%. The third stage of “knitting” with a rate of 16.9%, followed by the fourth stage of “cutting and straightening” the fabric with a rate of 12.9%, and the fifth place was the “design and pattern preparation” stage with a rate of 10.7%, followed by the sixth stage is the “interlocking” stage with a rate of 7.1%, followed by the seventh stage of “ironing and packaging” with a rate of 5.2%. The study recommended focusing on inserting sustainable practices in the stages of production of ready-made clothes, as it is the main factor at the present time to ensure profit and competitive position and preserve the environment around us.